1996
DOI: 10.1063/1.362860
|View full text |Cite
|
Sign up to set email alerts
|

Interdiffusion of lateral composition modulated (GaP)2/(InP)2 short-period superlattices with different encapsulants

Abstract: The interdiffusion of lateral composition modulated (GaP)2/(InP) 2 short-period superlattices (SPSs) is reported. The lateral composition modulation is achieved by the strain induced lateral layer ordering (SILO) process. A blueshift in the interband transition is observed by photoluminescence spectroscopy for capless and SiO 2 encapsulated annealed SPSs (800 °C, 5.5 h), while the intensity and wavelength of Si3N4 encapsulated annealed SPSs are only slightly perturbed. From transmission electron microscopy, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Because of its non-invasive nature, tympanic thermometry has been used as the most favoured measurement process during the last two decades. However, although researchers have assumed that tympanic temperature is a valid measure of body's core temperature (e.g., Sato et al, 1996), it has more recently been found that it best reflects brain temperature (e.g., Kirk, Rainey, Vail, & Childs, 2009;Newsham, Saunders, & Nordin, 2002). Due to the existence of automatic physiological mechanisms that cool the brain during hyperthermia (Cabanac, 1993), one problem with brain temperature is that it shows only little variability during physical exercise, thus making it hard to statistically demonstrate significant effects of temperature fluctuations on self-reported pleasure-displeasure.…”
mentioning
confidence: 99%
“…Because of its non-invasive nature, tympanic thermometry has been used as the most favoured measurement process during the last two decades. However, although researchers have assumed that tympanic temperature is a valid measure of body's core temperature (e.g., Sato et al, 1996), it has more recently been found that it best reflects brain temperature (e.g., Kirk, Rainey, Vail, & Childs, 2009;Newsham, Saunders, & Nordin, 2002). Due to the existence of automatic physiological mechanisms that cool the brain during hyperthermia (Cabanac, 1993), one problem with brain temperature is that it shows only little variability during physical exercise, thus making it hard to statistically demonstrate significant effects of temperature fluctuations on self-reported pleasure-displeasure.…”
mentioning
confidence: 99%